Several Issues Concerning the Relationship between the Central Government of the People’s Republic of China and the Hong Kong Special Administrative Region - Jianfan, Wu (Columbia Journal of Asian Law, 1988)
The Basic Law for the Special Administrative Region of Hong Kong (Basic Law) devotes one chapter to the relationship between the Central Government of the People’s Republic of China (PRC) and the Hong Kong Special Administrative Region (SAR). As this author understands it, the term “relationship between the Central Government and the Hong Kong SAR” refers to the relationship engendered by the Central Government’s exercise of jurisdiction over the Hong Kong SAR. In general, this relationship can be divided into three kinds of situations: First, affairs affecting national sovereignty and the overall interests of the nation as a whole shall be managed by the Central Government, and the Hong Kong SAR must submit to the leadership of the Central Government. Second, local matters of the Hong Kong SAR shall be managed by the Hong Kong SAR itself, but some of these local matters will be overseen by the Central Government. Third, other local matters shall be managed by the Hong Kong SAR without interference by the Central Government. The task of the Basic Law is to clearly delineate these three categories so that the Central Government and the Hong Kong SAR will have rules to follow in handling affairs which involve their relationship.